47.0k views
0 votes
Directions: Simplify each expression by combining like terms

1.) -y+9z-16y-25z
2.) 6x +3y-y+2+2
3.) 9b + 5(b - 4) + 15

4.) -4(3x + 5) + 10x + 1
5.) 0.5(y + 4) + 18y - 9
6.) -0.7r+9(-r-15)

User GayleDDS
by
5.4k points

2 Answers

3 votes

Answer:

wait idk

Explanation:

User Soulprovidr
by
4.6k points
6 votes

Answers:

1.) -y+9z-16y-25z = -17y-16z

2.) 6x +3y-y+2+2 = 6x+2y+4

3.) 9b + 5(b - 4) + 15 = 14b-5

4.) -4(3x + 5) + 10x + 1 = -2x-19

5.) 0.5(y + 4) + 18y - 9 = 18.5y-7

6.) -0.7r+9(-r-15) = -9.7r-135

User Nemanja Grabovac
by
4.5k points